Drug design : structure- and ligand-based approaches - Merz, Kenneth M., 1959-; Ringe, Dagmar; Reynolds, Charles H., 1957- (Cambridge [U.K.] ; New York : Cambridge University Press, 2010)
'Structure-based (SBDD) and ligand-based (LBDD) drug design are extremely important and active areas of research in both the academic and commercial realms. This book provides a complete snapshot of the field of computer-aided drug design and associated experimental approaches. Topics covered include X-ray crystallography, NMR, fragment-based drug design, free energy methods, docking and scoring, linear-scaling quantum calculations, QSAR, pharmacophore methods, computational ADME-Tox, and drug discovery case studies. A variety of authors from academic and commercial institutions all over the world have contributed to this book, which is illustrated with more than 200 images. This is the only book to cover the subject of structure and ligand-based drug design, and it provides the most up-to-date information on a wide range of topics for the practicing computational chemist, medicinal chemist, or structural biologist'--Provided by publisher
Machine generated contents note: 1. Computational chemistry in drug discovery William L. Jorgensen; Part I. Structural Biology: 2. X-Ray crystallography Gregory Petsko and Dagmar Ringe; 3. Fragment-based approaches to structural biology Stephen K. Burley, Gavin Hirst, Paul Sprengeler, and Siegfried Reich; 4. Application of NMR in drug discovery Christopher A. Lepre, Peter J. Connolly, and Jonathan M. Moore; Part II. Computational Chemistry Methodology: 5. Free energy calculations in structure-based drug design Michael R. Shirts, David L. Mobley, and Scott P. Brown; 6. Molecular dynamics in structure-based drug design Fangyu Ding and Carlos Simmerling; 7. Docking: a domesday report Martha S. Head; 8. Quantum mechanics in drug discovery Kenneth M. Merz; 9. Pharmacophore methods Steven L. Dixon; 10. QSAR in drug discovery Alexander Tropsha; 11. ADME-Tox William J. Egan; Part III. Applications to Drug Discovery: 12. Principles of computer-aided drug design Charles H. Reynolds; 13. Case study: p38 Arthur M. Doweyko; 14. HIV protease: de;j...-vu all over again M. Katharine Holloway, Nigel J. Liverton, John A. McCauley, Michael T. Rudd, John W. Butcher, Steve S. Carroll, Jillian DiMuzio, Christine Fandozzi, Kevin F. Gilbert, Shi-Shan Mao, Charles J. MacIntyre, Kevin T. Nguyen, Joseph J. Romano, Mark Stahlhut, Bang-Lin Wan, David B. Olsen, and Joseph P. Vacca; 15. Purine nucleoside phosphorylases as targets for transition-state analogue design Andrew S. Murkin and Vern L. Schramm; 16. GPCR 3D modeling Frank U. Axe; 17. Structure based design of potent glycogen phosphorylase inhibitors Qiaolin Deng
Includes bibliographical references and index.
Keywords: Drug Design; Ligands; Structure-Activity Relationship